The Time-Cost Trade-off to Manage A Project in a Fuzzy Environment - محنة, رؤيا سرحان; خلف, وقاص سعد (Journal of Economics and Administrative Sciences, 2019)
In this research, the problem of ambiguity of the data for the project of establishing the typical reform complex in Basrah Governorate was eliminated. The blurry of the data represented by the time and cost of the activities was eliminated by using the Ranking function and converting them into normal numbers. Scheduling and managing the Project in the Critical Pathway (CPM) method to find the project completion time in normal conditions in the presence of non-traditional relationships between the activities and the existence of the lead and lag periods. The MS Project was used to find the critical path. The results showed that the project completion time (1309.5) dinars and the total cost has reached (33113017769) dinars and then used another method, the method of time-cost exchange (TCT), which is one of the important techniques used by the project manager to shorten the time of completion of the project at the lowest cost has been achieved This method reduced the implementation time of the project by a large percentage. The results showed that the implementation period was reduced from (1309.5) days to (1224.2) days, and the cost of completion of (33353514407) dinars, an increase of (240496638) dinars.